2015
DOI: 10.1007/s00382-015-2912-7
|View full text |Cite
|
Sign up to set email alerts
|

Projected response of East Asian summer monsoon system to future reductions in emissions of anthropogenic aerosols and their precursors

Abstract: 850 hPa are enhanced over eastern and southern China and the surrounding oceans, and the East Asian subtropical jet shifted northward due to the decreases of aerosols. These factors also indicate enhanced EASM circulation, which in turn causes a 10 % increase in summer mean precipitation averaged over the EAMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…Our results clearly suggest that one pathway aerosol forcings have to affect the EASM is by changing the land-sea surface thermal contrast, as shown in previous studies (e.g., Liu et al, 2011;Zhang et al, 2012;Salzmann et al, 2014;Wang et al, 2015Wang et al, , 2016. However, we also emphasize the role of the EASJ, which could amplify or offset the effects of the surface thermal contrast.…”
Section: Discussionsupporting
confidence: 88%
“…Our results clearly suggest that one pathway aerosol forcings have to affect the EASM is by changing the land-sea surface thermal contrast, as shown in previous studies (e.g., Liu et al, 2011;Zhang et al, 2012;Salzmann et al, 2014;Wang et al, 2015Wang et al, , 2016. However, we also emphasize the role of the EASJ, which could amplify or offset the effects of the surface thermal contrast.…”
Section: Discussionsupporting
confidence: 88%
“…This is because changes in climate extremes are also likely driven by changes in large-scale atmospheric circulation (Haylock and Goodness 2004; Cassou et al 2005). Wang et al (2015b) suggested that the future reduction in anthropogenic aerosol emissions would greatly enhance East Asian summer monsoon circulation and precipitation. This may also contribute to the increases in precipitation extremes over China.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, legislation has been introduced by governments worldwide to reduce the emissions of aerosols and their precursors and improve air quality in recent years (Cofala et al 2007;Moss et al 2010). There will be a substantial effect on future climate change due to the aerosol reduction (Rotstayn et al 2013;Wang et al 2015b). We explore the effect of reduced aerosol emissions on climate extremes over China under future scenarios by contrasting the projected results from the CESM1 ensemble simulations under the RCP8.5 and RCP8.5 with fixed aerosol emissions scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…considered to be non-hygroscopic. The coupled model has been introduced, evaluated, and used in many studies of the radiative forcings and climatic effects of aerosols (e.g., Zhang et al, 2014aZhang et al, , 2016Wang et al, 2015b;Zhao et al, 2014). Three groups of experiments were conducted (Table 1), named CLI, EL, and LA (climatological means, El Niño and La Niña), with each group including 20 members by altering initial conditions.…”
Section: Model Description and Experimental Setupmentioning
confidence: 99%